2005
DOI: 10.1158/0008-5472.can-05-0220
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitivity Enhancement by Celecoxib, a Cyclooxygenase (COX)-2 Selective Inhibitor, via COX-2–Dependent Cell Cycle Regulation on Human Cancer Cells Expressing Differential COX-2 Levels

Abstract: To characterize the radiation-enhancing effects on human cancer cells and underlying mechanisms of celecoxib, a cyclooxygenase (COX)-2 selective inhibitor, and to ascertain whether its effects are COX-2 dependent. Clonogenic cytotoxicity assays and radiation survival assays after treatment with celecoxib F radiation were done on four human cancer cell lines that expressed differential COX-2 levels. Stably COX-2 knocked down or overexpressed cell lines were developed, and clonogenic assays, apoptosis assays, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 28 publications
3
82
1
Order By: Relevance
“…Both HCT-116 colon adenocarcinoma cells and NCI-H460 lung large cell carcinoma cells express low levels of endogenous COX-2 (21). Interestingly, we found that ectopically overexpressed COX-2 down-regulated EGFR expression in both of these cancer cell lines, whereas knockdown of endogenous COX-2 in MOR-P cells resulted in increased EGFR expression (Fig.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Both HCT-116 colon adenocarcinoma cells and NCI-H460 lung large cell carcinoma cells express low levels of endogenous COX-2 (21). Interestingly, we found that ectopically overexpressed COX-2 down-regulated EGFR expression in both of these cancer cell lines, whereas knockdown of endogenous COX-2 in MOR-P cells resulted in increased EGFR expression (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, we also developed a NCI-H460 cell line constitutively overexpressing COX-2 (H460-COX-2; refs. 21,22) and did the same comparison. EGFR expression in H460-COX-2 cells was also found to be down-regulated compared with mock cells much as it was in the HCT-116-COX-2 cells (Fig.…”
Section: Cox-2 Negatively Regulates Egfr Expressionmentioning
confidence: 98%
“…Therefore, our observations that COX-2 enhances the activity of ATR and its substrates, including Chk1 and p53, may be important to understand the various roles of COX-2 in cells. In addition, it may serve as an underlying mechanism for our previous observations that COX-2-overexpressing cells showed prolonged IR-induced G 2 arrest (29). Prolongation of G 2 arrest after IR has been reported in AT cells and is known as "G 2 accumulation" (37).…”
Section: Discussionmentioning
confidence: 86%
“…To investigate whether PGE 2 , a major end product of COX-2, is associated with ERK activation, cells were treated with 500 nmol/L PGE 2 . A concentration of 500 nmol/L PGE 2 is equivalent to the maximum inducible concentration in A549 cells, which have higher expression levels of COX-2 compared with those of HCT116 cells, and this amount, although sufficient to exert a considerable effect, does not exceed its physiologic range (29).…”
Section: Cox-2 Regulates Erk Activation Via Pgementioning
confidence: 99%
See 1 more Smart Citation